Tetrathiocyanozincate- and tetrathiocyanocobaltate-selective electrodes with low detection limits - Matveichuk, Yulya V.; Rakhman’ko, Evgenii M.; Akayeu, Yauhen B.; Zhilko, Vyacheslav V. (Journal of the Belarusian State University. Chemistry, 2017)
It was found that tetrathiocyanozincate- and tetrathiocyanocobaltate-selective electrodes based on steric hindered quaternary ammonium salt – 3,4,5 trisdodecyloxybenzyltrioctadecylammonium bromide (5 wt. %), dibutylphthalate – plasticizer (62 wt. %) with an internal solution containing 1 ⋅ 10– 4 mol/L of Zn2+ and 1 ⋅ 10–2 mol/L KCNS for tetrathiocyanozincate-selective electrodes or 1 ⋅ 10– 4 mol/LCo2+ and 0.1 mol/L for tetrathiocyanocobaltate-selective electrodes allow to determine of zinc or cobalt on the level 2 ⋅ 10–7 mol/L. It also eliminates the use of a volatile and carcinogenic membrane plasticizers and becomes to possible of measure the potential of the electrode system in the solutions at any concentration sequence. It is shown that the «washing» of electrodes before measurement with distilled water is undesirable because it leads to overestimation of the low detection limit.
Keywords: tetrathiocyanozincate- and tetrathiocyanocobaltate-selective electrodes; quaternary ammonium salt; plasticizer